Clinical Impact of a Pharmacist-Driven Prospective Audit with Intervention and Feedback on the Treatment of Patients with Bloodstream Infection - Naoto Okada; Momoyo Azuma; Kaito Tsujinaka; Akane Abe; Mari Takahashi; Yumiko Yano; Masami Sato; Takahiro Shibata; Mitsuhiro Goda; Keisuke Ishizawa (MDPI AG, 2022)
Evidence for the utility of pharmacist-driven antimicrobial stewardship programs remains limited. This study aimed to evaluate the usefulness of our institutional pharmacist-driven prospective audit with intervention and feedback (PAF) on the treatment of patients with bloodstream infections (BSIs). The effect of pharmacist-driven PAF was estimated using an interrupted time series analysis with a quasi-experimental design. The proportion of de-escalation during BSI treatment increased by 44% after the implementation of pharmacist-driven PAF (95% CI: 30-58, p < 0.01). The number of days of therapy decreased by 16 per 100 patient days for carbapenem (95% CI: −28 to −3.5, p = 0.012) and by 15 per 100 patient days for tazobactam/piperacillin (95% CI: −26 to −4.9, p < 0.01). Moreover, the proportion of inappropriate treatment in empirical and definitive therapy was significantly reduced after the implementation of pharmacist-driven PAF. Although 30-day mortality did not change, compliance with evidenced-based bundles in the BSI of Staphylococcus aureus significantly increased (p < 0.01). In conclusion, our pharmacist-driven PAF increased the proportion of de-escalation and decreased the use of broad-spectrum antibiotics, as well as the proportion of inappropriate treatment in patients with BSI. This indicates that pharmacist-driven PAF is useful in improving the quality of antimicrobial treatment and reducing broad-spectrum antimicrobial use in the management of patients with BSI.